Client Satisfaction towards Quality of Health Services: An Assessment at Primary Healthcare of District Gujranwala - Kauser Aftab Khan; Shahzad Ali Khan; Zubia Qureshi; Moazzam Ali Khan; Fouzia Nadeem Gill; Mudassar Mushtaq Jawad Abbasi (Intelektual Pustaka Media Utama, 2017)
This survey designed to evaluate the satisfaction level and the factors that affect the patient satisfaction regarding health care delivery services with the aim to improve the services in the primary health care settings of Gujranwala. A Cross Sectional Study done on randomly selected patients attending the basic health units of Gujranwala, with more than18 years of age. Pretested structured